P.014 OnabotulinumtoxinA-treated cervical dystonia patients report improvements in health-related quality of life in a prospective, observational study: POSTURe. (5th June 2019) - Petitclerc, M; Cloutier, M; Bhogal, M; Davidovic, G
Abstract : Background: The clinical benefit of onabotulinumtoxinA in cervical dystonia (CD) is proven, but its impact on health-related quality of life (HRQoL) is largely unknown.Methods: Multicentre, prospective, observational study (NCT01655862) of CD patients treated with onabotulinumtoxinA at physician discretion (maximum 9 treatments). Patient-reported HRQoL outcomes and work productivity were collected at baseline, 4- or 8-weeks post-treatment, and final visit (prior to 9 th treatment). OnabotulinumtoxinA utilization was assessed.Results: 61 patients received ≥1 treatment; 74.1% completed all treatments. Average total dose/treatment was 186.9U. The splenius capitis was most frequently treated (100% patients). Average pain numeric rating scale score was significantly improved at final visit (2.1) versus baseline (4.6; p<0.001) as were CD impact profile questionnaire-58 scores across all subscales (head/neck symptoms, pain/discomfort, sleep, upper limb activities, walking, annoyance, mood, psychosocial functioning; all p<0.001). Fewer patients (16.0%) reported loss of work productivity at final visit versus baseline (48.4%). 121 AEs were reported by 67.2% patients. 62 AEs in 44.3% patients were treatment-related, the most common being neck pain (18%). One serious AE (not treatment-related) was reported by 1 patient. No new safety signals were identified.Conclusions: Long-term use of onabotulinumtoxinA is a safe, effective treatment for CD, improving HRQoL and work productivity.